Home nasogastric tube program for NICU infants: a seven year retrospective outcome analysis - Weninger, Alexa; Sabella, Mikayla; Sahmoun, Abe E.; Mohamed, Mohamed W.; Forward, Brennan; Brower-Breitwieser, Carrie M. (Frontiers in Pediatrics, 2025)
ObjectivesThe goal of this study was to assess the safety and effectiveness of a Home Nasogastric Program for infants admitted to a Neonatal Intensive Care Unit (NICU).Study designWe performed a retrospective chart review of infants discharged from a Level III NICU to a Home Nasogastric (HNG) follow-up clinic from December 2014-February 2022. Data was recorded for two years post discharge from the NICU.Results83 infants were included in this study. There were no emergency department visits related to feeding tube dysfunction or nasogastric (NG) tube equipment malfunctions. The number of days the NG tube was used median (IQR): 3 (2–10). Seventy-seven (93%) infants had no documented feeding problems at the end of the follow-up period. We estimate 556 hospitalization days avoided resulting in cost savings.ConclusionThe Home NG program was safe and effective. This program decreased length of NICU stay and health care associated costs.